A Hollow-Core Photonic Crystal Fiber-Based SPR Sensor With Large Detection Range - Nannan Luan; Jianquan Yao (IEEE Photonics Journal)
We propose a large detection range surface plasmon resonance (SPR) sensor based on hollow-core photonic crystal fiber in this paper. The sensor consists of an analyte channel in the core hole and a silver nanowire in the cladding holes. We investigate the resonance properties between the core modes and the surface plasmon polariton (SPP) modes excited on the nanowire surface in a large refractive index (RI) range from 1.33 to 1.5. Numerical results show that the resonance between the core mode and the higher order SPP modes can occur at particular wavelengths, thus exciting resonance peaks that shift to short wavelengths as RI increases. By tracking most sensitive peak, which is formed by the resonance combination of the x-polarized core mode and the second-order SPP mode, our sensor can measure large RI ranges of the analyte either higher or lower than that of the fiber material.